THE INFLUENCE OF QUALITY OF WORK-LIFE AND STAYING INTENTION THROUGH JOB SATISFACTION ON MILENIAL WORKERS IN THE BANKING SECTOR IN SURABAYA - Prince Wicaksono Purba; Noviaty Kresna Darmasetiawan (Jurnal Ekonomi, 2023)
The purpose of this research is to determine the influence of Quality of Work Life on the intention to leave among millennial employees in state-owned banking sector in Surabaya. This type of research is basic research, which provides solutions to a specific problem and validates existing theories. Employees have a balanced time between work and family according to their needs. Having a good quality of work life can increase job satisfaction and help organizations retain their employees. The satisfaction felt by employees then manifests in a lower desire to leave the company. Based on data processing, hypothesis testing, and discussion, the researcher concludes that the four hypotheses are supported. Quality of Work Life has a negative and significant impact on the intention to leave among millennial employees in state-owned banking sector in Surabaya. Quality of Work Life has a positive and significant impact on job satisfaction among millennial employees in state-owned banking sector in Surabaya. Job satisfaction has a negative and significant impact on the intention to leave among millennial employees in state-owned banking sector in Surabaya. Quality of Work Life has a significant impact on the intention to leave through job satisfaction as a mediating variable among millennial employees in state-owned banking sector in Surabaya.